2015
DOI: 10.1088/0031-9155/60/21/8275
|View full text |Cite
|
Sign up to set email alerts
|

Image reconstruction in higher dimensions: myocardial perfusion imaging of tracer dynamics with cardiac motion due to deformation and respiration

Abstract: Myocardial perfusion imaging (MPI) using slow rotating large field of view cameras requires spatiotemporal reconstruction of dynamically acquired data to capture the time variation of the radiotracer concentration. In vivo, MPI contains additional degrees of freedom involving unavoidable motion of the heart due to quasiperiodic beating and the effects of respiration, which can severely degrade the quality of the images. This work develops a technique for a single photon emission computed tomography (SPECT) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…(Second Row) The coronal view of the reconstruction of dynamic data 30 sec after the injection of 99m Tc-tetrofosmin. The reconstruction of the gated cardiac data was performed using a 5D spatiotemporal reconstruction algorithm described in [7]. In this simulation, 6 B-spline basis functions were used for the temporal changes in the tracer concentration and 8 Gaussian basis functions were used for the cardiac deformation due to the heart beating.…”
Section: Figmentioning
confidence: 99%
“…(Second Row) The coronal view of the reconstruction of dynamic data 30 sec after the injection of 99m Tc-tetrofosmin. The reconstruction of the gated cardiac data was performed using a 5D spatiotemporal reconstruction algorithm described in [7]. In this simulation, 6 B-spline basis functions were used for the temporal changes in the tracer concentration and 8 Gaussian basis functions were used for the cardiac deformation due to the heart beating.…”
Section: Figmentioning
confidence: 99%
“…Algorithms have advanced, including modeling of cardiac motion in dynamic 5D reconstruction, modeling of cardiac and respiratory motion in dynamic 6D reconstruction, and directly fitting compartment models . Our SIFADS method is a 4D reconstruction approach that directly estimates time activity curves (TACs) from projections of dynamic data acquired from slowly rotating gamma cameras and differs from these previous methods where first dynamic image frames are reconstructed, and then, from which TACs can be generated.…”
Section: Introductionmentioning
confidence: 99%
“…36 Our work does not address cardiac or any motion at this stage. 28,29,37 The paper is organized as follows. In Section 2, we present the algorithm and some measures that we use in the current work to evaluate the algorithm's performance.…”
mentioning
confidence: 99%
“…6 Their study takes advantage of a unique '4D reconstruction' method for dynamic SPECT imaging, specially developed inhouse for cardiac perfusion imaging. 4 This type of advanced parametric image reconstruction represents the measured data as a combination of pre-defined timeactivity curves (also called shape or basis functions) for every voxel in the field of view. While there is not yet an accepted 'standard basis' for 4D image reconstruction, the authors have shown promising results using their chosen shape functions in several earlier simulation and human studies.…”
mentioning
confidence: 99%
“…While there is not yet an accepted 'standard basis' for 4D image reconstruction, the authors have shown promising results using their chosen shape functions in several earlier simulation and human studies. [3][4][5] If these shape functions can provide a good fit to the measured dynamic data, then the modeled tracer distribution or 'parametric images' can be visualized post hoc at any time point from the start to end of the scan. This has the potential to allow visualization of tracer uptake in very short time intervals (i.e., 5 seconds in the present study) but with the image quality and count statistics derived from the much longer dynamic scan.…”
mentioning
confidence: 99%